CONSIDERAȚII DESPRE DIPLOMAȚIA CULTURALĂ A MICROSTATELOR - Jora, Lucian (Revista de Știinţe Politice şi Relaţii Internaţionale)
Cultural diplomacy is intrinsically linked to Soft Power, defined as the persuasion capacity of one’s own culture in the IR system. Unlike Hard Power, Soft Power is not the exclusive prerogative of large states, the most representative example being the Vatican’s influence capacity in IR. Public diplomacy/Cultural diplomacy thus becomes an instrument through which microstates can have a role and a voice in the IR concert. This article intends to analyze the Soft Power projection capabilities through public diplomacy and cultural diplomacy for three microstates in Europe, namely Andorra, San Marino and Liechtenstein.